The immediate effects of individual thai yoga on back flexibility in the elderly - ขันทอง, ภักศจีภรณ์; สุขโท, สุภารัตน์; พันธ์พรหม, ศุภรัตน์; แทนหอม, ขวัญฤทัย; ระหาร, วิศิษฐ์ชัย (UBRU Journal for Public Health Research, 2019)
This Quasi –Experimental research aimed to studies the immediate effects of Thai Yoga or Ruesi Dudton in individual posture on back flexibility of the elderly in Muang, Ubon Ratchathani Province, Thailand. There were 60 healthy elderly who participated in this research. The study protocol was sampling 10 participants into 6 groups. There were 1 control and 5 experimental groups (5 postures). Before and after participation, the researchers will measure the flexibility by Sit and reach box and Schober. Data analysis were used descriptive statistic to find mean and standard deviation, Kruskal-Wallis H was analyzed for group different in demographic data, one way ANOVA was analyzed for differences between group, and Wil coxon sign range test was analyzed for pre and post of Sit and Reach Test and Schober Test. The results showed no significant difference between group but found immediately significant difference between pre and post measurement for Sit and Reach Test were control group, posture 1, 3, 4, and 5 (p < 0.05) and found significant difference in posture 1-5 except in the control group in Schober Test (p < 0.05). In conclusion, increasing of back flexibility in the elderly required the timing for improvement.